(untitled) (CIPEEX, 2022)
INTRODUCTION: REGULAR EXERCISES, SUCH AS RUNNING, DIRECTLY INFLUENCE THE IMPROVEMENT OF MAXIMAL OXYGEN CONSUMPTION (VO2MAX). VO2MAX IS CONSIDERED ONE OF THE MAIN INDICATORS OF AEROBIC POWER AND THE MAINTENANCE OF ADEQUATE LEVELS OF CARDIORESPIRATORY FITNESS ARE RECOGNIZED FOR BRINGING HEALTH BENEFITS, ACTING IN THE PREVENTION OF CARDIOVASCULAR AND CARDIORESPIRATORY DISEASES, OBESITY AND STRESS.